2019
DOI: 10.1126/scitranslmed.aau7116
|View full text |Cite
|
Sign up to set email alerts
|

Identification of entacapone as a chemical inhibitor of FTO mediating metabolic regulation through FOXO1

Abstract: Recent studies have established the involvement of the fat mass and obesity-associated gene (FTO) in metabolic disorders such as obesity and diabetes. However, the precise molecular mechanism by which FTO regulates metabolism remains unknown. Here, we used a structure-based virtual screening of U.S. Food and Drug Administration–approved drugs to identify entacapone as a potential FTO inhibitor. Using structural and biochemical studies, we showed that entacapone directly bound to FTO and inhibited FTO activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
202
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(208 citation statements)
references
References 81 publications
5
202
0
1
Order By: Relevance
“…Moreover, these mice show increased energy expenditure when fed HFD and maintained under room temperature. These results are in line with the fact that FOXO1 promotes Atgl expression but suppresses Ucp1 transcription (Nakae et al 2008(Nakae et al , 2012Chakrabarti and Kandror 2009b;Chakrabarti et al 2011;Liu et al 2016;Kita et al 2019;Peng et al 2019). Therefore, it appears that at least upon HFD feeding, suppression of Ucp1 expression and energy expenditure would play a dominant role over ATGL-dependent lipolysis.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Moreover, these mice show increased energy expenditure when fed HFD and maintained under room temperature. These results are in line with the fact that FOXO1 promotes Atgl expression but suppresses Ucp1 transcription (Nakae et al 2008(Nakae et al , 2012Chakrabarti and Kandror 2009b;Chakrabarti et al 2011;Liu et al 2016;Kita et al 2019;Peng et al 2019). Therefore, it appears that at least upon HFD feeding, suppression of Ucp1 expression and energy expenditure would play a dominant role over ATGL-dependent lipolysis.…”
Section: Discussionsupporting
confidence: 75%
“…We and others showed that FOXO1 promotes the expression of Atgl (Chakrabarti and Kandror 2009b;Chakrabarti et al 2011;Jung et al 2019). Interestingly, a number of reports showed that FOXO1 suppresses the expression of genes regulating energy dissipation, including UCP1, in white and brown adipocytes (Nakae et al 2008(Nakae et al , 2012Liu et al 2016;Kita et al 2019;Peng et al 2019). However, a recent study indicated that in brown adipose tissue of mice fed ND, FOXO1 does not affect UCP1 and in vitro under specific culture conditions deletion of FOXO1 might even decrease Ucp1 expression in brown adipocytes (Jung et al 2019).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Currently, several promising agents may have potentials to treat MDs by targeting m 6 A, such as m 6 A inhibitors. It is known that FTO negatively regulated m 6 A levels and positively regulated adipogenesis, thus we can use FTO inhibitors (rhein, radicicol, epigallocatechin gallate, entacapone and meclofenamic acid) [91,136,[138][139][140] to remove the potential effect of FTO. In addition, ALKBH5 is positively related to the frequent immune reactions [123], if we rule out the effects of ALKBH5 on immune cells via using ALKBH5 inhibitor (IOX3) [141], the immune-related MDs will be improved.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, scientist have newly identified entacapone, an inhibitor of catechol-O-methyltransferase applied for treatment of Parkinson's disease, as a chemical FTO inhibitor (87). Entacapone elicits effects on metabolic homeostasis through selectively targeting FTO activity, whereas its function in tumorigenesis remains to be elucidated.…”
Section: Clinical Relevance Of M 6 A-targeted Strategymentioning
confidence: 99%